Assessment of left atrium and diastolic dysfunction in patients with hypertensive retinopathy: A real-time three-dimensional echocardiography-based study - TİGEN, MUSTAFA KÜRŞAT (TAYLOR & FRANCIS INC, 2017)
The fundoscopic examination of hypertensive patients, which is established hypertension-related target organ damage (TOD), tends to be underutilized in clinical practice. We sought to investigate the relationship between retinal alterations and left atrium (LA) volumes by means of real-time three-dimensional echocardiography (RT3DE). Our population consisted of 88 consecutive essential hypertensive patients (age 59.2 +/- 1.2 years, 35 males). All subjects underwent a fundoscopy examination and were distributed into four groups according to the Keith-Wagener-Barker (KWB) classification. The four groups (KWB grades 0-3: including 26, 20, 26, and 16 patients, respectively) did not differ with regard to age, gender, or metabolic profile. There were no significant differences between groups with regard to parameters reflecting LV systolic function and diastolic dysfunction (DD) in two-dimensional echocardiography (2DE). Nevertheless, patients in the higher KWB category had higher values of LA volumes (LA maximal volume index, LA minimal volume index, preatrial contraction volume index, LA total stroke volume index, LA active stroke volume index, p < 0.001) regarding RT3DE. There is also a significant relationship between LA active stroke volume index (ASVI) and duration of hypertension (HT) (r: 0.68, p < 0.001). In the logistic regression analysis, ASVI was independent predictors of LV DD in patients with arterial hypertension (HT). Patients with arterial HT were found to have increased LA volumes and impaired diastolic functions. Assessment of the arterial HT patient by using RT3DE atrial volume analysis may facilitate early recognition of TOD, which is such a crucial determinant of cardiovascular mortality and morbidity.
Keywords: Arterial hypertension; diastolic dysfunction; hypertensive retinopathy; left atrial volume; three dimensional echocardiography; RETINAL MICROVASCULAR ABNORMALITIES; HEART-FAILURE; ARTERIAL-HYPERTENSION; ANTIHYPERTENSIVE TREATMENT; PRACTICE GUIDELINES; EJECTION FRACTION; RISK; MANAGEMENT; DISEASE; VOLUME